A method for determining the constitutive model of the heat-affected zone using digital image correlation. (1st August 2022) - Yan, Rui; Xin, Haohui; Yang, Fei; El Bamby, Hagar; Veljkovic, Milan; Mela, Kristo
Graphical abstract: Highlights: The HAZ stress–strain relationship measured from butt-welded coupons has a higher strength than under the uniaxial tensile stress state. A linear modification factor is proposed to modify the measured HAZ stress–strain relationship at the plastic stage before necking. The load-deformation relationship and the strain distribution along the loading direction are used to calibrate the modification factor. Using the measured original stress–strain relationship, FEA overestimates the ultimate resistance slightly but overestimates the peak deformation significantly. Using the modified stress–strain relationship, FEA predicts the ultimate resistance and the peak deformation very well. Abstract: The heat-affected zone (HAZ) is an unmelted region of a welded joint that has changed in material properties because of high temperatures during the welding process. HAZ has a lower strength than the base (parent) material (BM) and the weld metal (WM). The lower material strength is more significant if BM is made of high strength steel and the undermatching filler metal is used. Therefore, the constitutive model of HAZ is essential for predicting the mechanical behaviour of the welded joint. In this paper, a method for determining the true stress–strain relationship of HAZ is proposed. The effect of the transverse constraint on the longitudinal deformation of HAZ imposed by BM and/or WM is eliminated by a linear modification factor correlating to the true strain. Standard tensile coupon tests were used to obtain the constitutive model of HAZ using digital image correlation (DIC). The modification factor proposed for reducing the true stress is calibrated based on finite element analysis (FEA). The modified constitutive model of HAZ is validated against the experimental results obtained by DIC. The validated HAZ material property can be used in advanced numerical simulation of welded joints.